Burgenland Croats and Burgenland Croatian - Samardžija, Marko (Poznańskie Studia Slawistyczne, 2015)
The paper concerns the formation of the Croatian ethnic community in the Austro-Hungarian region in the 16th century, the author tracks the development of the literary language of the Croats in western Hungary since the 1750s and monitors establishing contacts with the literary language and orthography changes in Croatia in the second half of the 19th century. It was explained how the expressions Burgenland (Gradišće), Burgenland Croats (Gradišćanski Hrvati) and Burgenland Croatian language (gradišćanskohrvatski jezik) came to use after the first world war. The codification of Burgenland Croatian literary language is shown in 3 periods: 1. between the two world to the present. The main codification works (dictionaries, grammar books and orthography) in Burgenland Coratian literary language published after 1980s have been mentioned.